A retrieval-specific mechanism of adaptive forgetting in the mammalian brain. Issue 1 (December 2018) - Bekinschtein, Pedro; Weisstaub, Noelia; Gallo, Francisco; Renner, Maria; Anderson, Michael
Abstract Forgetting is a ubiquitous phenomenon that is actively promoted in many species. How and whether organisms' behavioral goals drive which memories are actively forgotten is unknown. Here we show that processes essential to controlling goal-directed behavior trigger active forgetting of distracting memories that interfere with behavioral goals. When rats need to retrieve particular memories to guide exploration, it reduces later retention of other memories encoded in that environment. As with humans, this retrieval-induced forgetting is competition-dependent, cue-independent and reliant on prefrontal control: Silencing the medial prefrontal cortex with muscimol abolishes the effect. cFos imaging reveals that prefrontal control demands decline over repeated retrievals as competing memories are forgotten successfully, revealing a key adaptive benefit of forgetting. Occurring in 88% of the rats studied, this finding establishes a robust model of how adaptive forgetting harmonizes memory with behavioral demands, permitting isolation of its circuit, cellular and molecular mechanisms. Forgetting is ubiquitous across the animal kingdom, but neuroscience is only beginning to address its mechanisms. This study shows that rats, like humans, actively forget memories that interfere with retrieval, and that this retrieval-induced forgetting requires the prefrontal cortex.